Brain endothelial specific gene therapy improves experimental Sandhoff disease. Issue 6 (June 2020) - Dogbevia, Godwin; Grasshoff, Hanna; Othman, Alaa; Penno, Anke; Schwaninger, Markus
In Tay-Sachs and Sandhoff disease, a deficiency of the lysosomal enzyme β-hexosaminidase causes GM2 and other gangliosides to accumulate in neurons and triggers neurodegeneration. Although the pathology centers on neurons, β-hexosaminidase is mainly expressed outside of neurons, suggesting that gene therapy of these diseases should target non-neuronal cells to reconstitute physiological conditions. Here, we tested in Hexb −/− mice, a model of Sandhoff disease, to determine whether endothelial expression of the genes for human β-hexosaminidase subunit A and B ( HEXA, HEXB ) is able to reduce disease symptoms and prolong survival of the affected mice. The brain endothelial selective vectors AAV-BR1-CAG- HEXA and AAV-BR1-CAG- HEXB transduced brain endothelial cells, which subsequently released β-hexosaminidase enzyme. In vivo intravenous administration of the gene vectors to adult and neonatal mice prolonged survival. They improved neurological function and reduced accumulation of the ganglioside GM2 and the glycolipid GA2 as well as astrocytic activation. Overall, the data demonstrate that endothelial cells are a suitable target for intravenous gene therapy of GM2 gangliosidoses and possibly other lysosomal storage disorders.